Primary Synovial Sarcoma of the Kidney - Shiu-Dong Chung; Kuo-How Huang; Shih-Chieh Chueh; Ming-Kuen Lai; Wei-Chou Lin (Journal of the Formosan Medical Association, 2008)
Primary synovial sarcoma arising from the kidney is extremely rare. We report two cases with primary renal synovial sarcoma. Both were initially diagnosed as renal cell carcinoma. The first case was a 30-year-old woman who presented with right flank soreness. Ultrasonography disclosed a multiloculated cystic tumor measuring 9 × 7 cm. She underwent hand-assisted laparoscopic radical nephrectomy; there was no recurrence during 15 months of follow-up. The second case was a 49-year-old woman who presented with a palpable mass in the left upper quadrant of the abdomen of 1 month's duration. Computed tomography showed a heterogeneously enhanced tumor measuring 13 × 11 cm at the left retroperitoneum with displacement of the pancreas and the left kidney. Hand-assisted retroperitoneoscopic radical nephrectomy was performed. She had no evidence of recurrence after 27 months of follow-up. Pathology of the two cases showed histologic and immunochemical features of synovial sarcoma with coexisting spindle and epithelial cells. Physicians should be aware of the possibility of malignancy in cystic renal masses and that synovial sarcoma is one of the possibilities.